The Effect of Certification Allowances and Commitment to Tasks on Teacher Work Performance - Tambingon, Henny; Lengkong , Jeffry Sony Junus; Rawis, Joulanda A.M.; Theno, Ignatius Rudi; Dondokambey, Rainier N; Wuwungan, Hansje T.; Liow, Evans S. (International Journal of Information Technology and Education, 2024)
This research aims to test 1) Whether or not there is an influence of allowances certification of teacher work performance at Bitung City State Middle School, 2) Whether there is or not The influence of commitment to tasks on teacher work performance in Bitung City State Middle School, 3) There is or No influence allowance certification And commitment on task to Performance Work In Bitung City State Middle School. Study This uses the method quantitative. Collection data were collected with a questionnaire and documentation. Data was analyzed descriptively using the SPSS version 16 for the Windows program. From the results research can be concluded that 1) There is an influence of certification allowance (X 1 ) on work performance (Y), 2) There is an influence of commitment to the task (X 2 ) on teacher work performance (Y), and 3) There is an influence of certification (X 1 ), and commitment to the task (X 2 ) on teacher work performance (Y) at Bitung City State Middle School. The deep implications of this research are: 1) Teacher certification is a program where teachers will be monitored and tested in a way periodically with the use of tool tests that have been set government. Certification Teacher will create a capable source Power teacher which is better. 2) Commitment to the duties of each teacher is very important because with commitment a teacher can become more responsible for his job. Teachers who own something committed will Work in a way optimal so that can pour out attention, thought, power, and time for their work so that what he has done follows what is expected by the school. 3) Teacher work performance is a contribution made by a person teachers towards their duties and functions through the totality of their abilities For reach national education goals.